2019
DOI: 10.24198/pjd.vol31no3.23794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 10% carbamide peroxide bleaching gels on surface hardness of nano filled composite resin

Abstract: Introduction: Home bleaching is the whitening treatment of vital teeth applied by patients themselves at home under dentist supervision. In clinical condition, several patients who need bleaching treatment already had nano filled composite resin restoration on their teeth. The purpose of this study was to investigate the contact time difference of 10% carbamide peroxide bleaching gels application for home bleaching on the surface hardness of nano filled composite resin activated by Light Emitting Diode (LED). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Bicer et al also found that microhardness of tested nanocomposites was not affected by bleaching with 16% carbamide peroxide and 30% hydrogen peroxide 16 . On the other hand, Mona D revealed that there is a decrease in microhardness of nanocomposites when treated with 10% carbamide peroxide 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Bicer et al also found that microhardness of tested nanocomposites was not affected by bleaching with 16% carbamide peroxide and 30% hydrogen peroxide 16 . On the other hand, Mona D revealed that there is a decrease in microhardness of nanocomposites when treated with 10% carbamide peroxide 24 .…”
Section: Discussionmentioning
confidence: 99%